Literature in primary schools: perceptions, challenges and pedagogical knowledge / Siti Norliana Ghazali ... [et al.] - Ghazali, Siti Norliana; Che Razali, Sulia Masturina; Razawi, Nurul Amilin; Mohamad, Faizah; Mohamad, Razita (2014)
Malaysia‟s education policy is aligned to its vision, which aims to become a fully developed nation by 2020. Some of the measures taken to achieve this vision are introducing ICT through the Smart school program and improving the proficiency of English in Malaysia by introducing literature as part of the English syllabus. Teachers‟ attitudes and perceptions play a key role in making sure that any initiative introduced by the Ministry of Education is successful. This paper aims to find out teachers‟ perceptions on teaching literature in primary schools and the challenges or difficulties faced by them. It also aims to investigate teachers‟ knowledge of literature and literature teaching methodology. Data was gathered using questionnaire distributed to teachers in Kemaman selected through cluster sampling and analyzed using SPSS. Results showed that teachers‟ attitudes towards literature were moderately positive. Teachers faced a number of problems and their knowledge of literature is moderate. Teacher variables do not significantly relate to their perceptions, problems and knowledge.